What determines adoption of E-banking among Nigerians? a conceptual approach / Maruf Gbadebo Salimon, Rushami Zien Yusoff and Sany Sanuri Mohd Mokhtar. - Salimon, Maruf Gbadebo; Yusoff, Rushami Zien; Mohd Mokhtar, Sany Sanuri (Universiti Teknologi Mara Selangor, 2016)
Extant studies in the field of consumer behavior and information technology acceptance have established that adoption of electronic banking is determined by several factors. While several of these studies emanate from developed nations, few are available in developing countries like Nigeria. Aside, most of these studies concentrate on intention to adopt and failed to find out why customers lack trust and do not satisfy with the services render to them. Hence, this study looks into issues of trust and satisfaction of e-banking adoption and their relationship with other determinants as this will help to increase the rate of adoption of e-banking that is generally low in Nigeria.